E-DBCM: A dynamically coupled upland and in-stream water quality model for watershed water quality simulation - Shen, Yanxia; Zhu, Zhenduo; Jiang, Chunbo (Frontiers in Water, 2022)
A dynamic bidirectional coupled modeling framework for water environment simulation (E-DBCM), consisting of an upland watershed model (UWSM) and a two-dimensional (2D) downstream waterbody model (DWBM), is developed. The UWSM is used to describe the rainfall runoff and determine the amount of pollutant load to the downstream waterbody, whereas the DWBM is used to simulate the 2D hydrodynamic and pollutant transport process in the downstream waterbody. The UWSM and DWBM are spatial connected through a moving boundary, which can ensure the mass and momentum conservation. The proposed E-DBCM is validated via three cases and the results show that the E-DBCM has satisfactory numerical accuracy, which can effectively reproduce the pollutant transport process and achieve good results in practical applications. The water environment in Yanqi River Basin is evaluated by the E-DBCM. The percent bias is about 10%, indicating that the proposed model is reliable and the simulation accuracy can satisfy the engineering demand. The water pollution problems in this basin are serious, especially during flood season, and both the TP and TN concentrations exceed the discharge standard of water pollutants in Beijing. It is necessary to take various measures to strengthen water environment treatment and protection in this basin.